Evidence for parapatric speciation in the Mormyrid fish, Pollimyrus castelnaui (Boulenger, 1911), from the Okavango-Upper Zambezi river systems: P. marianne sp. nov., defined by electric organ fischarges, morphology and genetics - Kramer, Bernd; Sauer-Gürth, Hedwig; Wink, Michael (Environmental biology of fishes, 2003)
We report on parapatric speciation in the mormyrid fish, Pollimyrus castelnaui (Boulenger, 1911), from the Okavango and the Upper Zambezi River systems. We recognise samples from the Zambezi River as a distinct species, P. marianne, displaying an eastern phenotype of electric organ discharge (EOD) waveform (Type 3) that is distinct from the western EOD phenotype (Type 1) observed in P. castelnaui samples from the neighbouring Okavango. Samples from the geographically intermediate Kwando/Linyanti River (a tributary of the Zambezi that is also intermittently connected to the Okavango) presented a more variable third EOD phenotype (Type 2). In 13 out of 14 morphological characters studied, the Zambezi River samples differed significantly from P. castelnaui. Morphologically and in EOD characters, the Kwando/Linyanti fish are distinct from both P. castelnaui and P. marianne. Sequence analysis of the mitochondrial cytochrome b gene unambiguously reveals that specimens from the Zambezi River System form a well supported taxon which clearly differs from P. castelnaui from the Okavango (1.5-2.5% sequence divergence). Within specimens from the Kwando-Zambezi System some geographic differentiation can be detected (nucleotide substitutions up to 0.6%); but groups cannot be resolved with certainty. Significant allozyme differences were found between the Okavango and all other EOD types from the Upper Zambezi System, and, within the Zambezi System, between the Kwando (Type 2) and Zambezi (Type 3) individuals. The low Wright's fixation index values, the lack of fixed allele differences, and small genetic distances provide little evidence for speciation between groups within the Zambezi System, but moderate to great fixation index values and significant allele frequency differences were observed between the Okavango and the other fishes. It is concluded that within the Zambezi System, differentiation between Kwando/Linyanti and Zambezi populations (as revealed by morphology and EOD waveform comparisons) is so recent that substantial genetic (allozyme and mitochondrial sequence) differences could not have evolved, or were not detected.